2023
DOI: 10.1002/hup.2871
|View full text |Cite
|
Sign up to set email alerts
|

Can antidepressant use be associated with emotional blunting in a subset of patients with depression? A scoping review of available literature

Muhammad Youshay Jawad,
Maurish Fatima,
Umer Hassan
et al.

Abstract: Introduction Despite frequent recognition of emotional blunting in the published literature, either as a primary symptom of depression or as an adverse effect of antidepressants, there is no systematic synthesis on this topic to our knowledge. We undertook this scoping review to assess the prevalence, clinical features, implicated causes and management of emotional blunting, outlining the phenomenological and clinical gaps in research. Method A systematic search was done until March 15, 2022, to include all or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…SSRIs function by reducing the reabsorption of serotonin into neurons and increasing intracellular serotonin levels (Etievant, Haddjeri, & Lau, 2020). They have downstream impacts on the dopamine system (Di Giovanni, Esposito, & Di Matteo, 2010) and are associated with a number of side effects, including sexual dysfunction (Rothmore, 2020) and a "blunting" of positive affect (Jawad et al, 2023).…”
Section: Romantic Love and Ssrismentioning
confidence: 99%
“…SSRIs function by reducing the reabsorption of serotonin into neurons and increasing intracellular serotonin levels (Etievant, Haddjeri, & Lau, 2020). They have downstream impacts on the dopamine system (Di Giovanni, Esposito, & Di Matteo, 2010) and are associated with a number of side effects, including sexual dysfunction (Rothmore, 2020) and a "blunting" of positive affect (Jawad et al, 2023).…”
Section: Romantic Love and Ssrismentioning
confidence: 99%
“…The latter has also been discussed in another study, where emotional blunting scores correlated with MADRS scores and were found to be lower in remitted than in nonremitted patients ( Aşçibaşi et al, 2020 ). Emotional blunting remains an important concern during antidepressant treatment ( Jawad et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%